Letter from James Curtis Booth to Samuel W. Levis, April 8, 1883 - Booth, James Curtis (1883)
James Curtis Booth (1810-1888) describes a property he wishes to sell to Samuel W. Levis.
Keywords: Booth, James Curtis, 1810-1888; Real property